Evaluation of tubulin β‐3 as a novel senescence‐associated gene in melanocytic malignant transformation. (7th March 2017) - Orfanidis, Kyriakos; Wäster, Petra; Lundmark, Katarzyna; Rosdahl, Inger; Öllinger, Karin
Summary: Malignant melanoma might develop from melanocytic nevi in which the growth‐arrested state has been broken. We analyzed the gene expression of young and senescent human melanocytes in culture and compared the gene expression data with a dataset from nevi and melanomas. A concordant altered gene expression was identified in 84 genes when comparing the growth‐arrested samples with proliferating samples. TUBB3, which encodes the microtubule protein tubulin β ‐3, showed a decreased expression in senescent melanocytes and nevi and was selected for further studies. Depletion of tubulin β ‐3 caused accumulation of cells in the G2/M phase and decreased proliferation and migration. Immunohistochemical assessment of tubulin β ‐3 in benign lesions revealed strong staining in the superficial part of the intradermal components, which faded with depth. In contrast, primary melanomas exhibited staining without gradient in a disordered pattern and strong staining of the invasive front. Our results describe an approach to find clinically useful diagnostic biomarkers to more precisely identify cutaneous malignant melanoma and present tubulin β ‐3 as a candidate marker.